Feed Management of Balinese Cattle in Post-Mining Land - Maulida, Anisa Risma; Mayulu, Hamdi; Daru, Taufan Purwokusumaning; Ardiansyah, Ardiansyah (INOVASI: Jurnal Ekonomi, Keuangan, dan Manajemen, 2025)
Reclaimed post-coal mining land holds potential for use as grazing areas and forage production. This research aimed to assess the potential and feed management strategies for Bali cattle (Bos sondaicus) on post-mining land. The study was conducted at the Pit Jupiter reclamation site of PT Kaltim Prima Coal using a combination of field observations and in-depth interviews. Vegetation sampling followed the Halls method with a 1m x 1m plate meter across 80 sampling points within a 67.28-hectare pasture divided into Pedok (site) 3 and Pedok 2. Soil samples, taken to analyze chemical properties, were collected using a random sampling method at 10 points at a depth of 0-20 cm. The potential of the pasture was evaluated based on soil fertility status, forage identification, importance value index (INP), forage production, and livestock carrying capacity. The vegetation included 32 species from 13 families, with Paitan grass (Paspalum conjugatum) being dominant, achieving the highest INP value of 95.12%. Feed management on the reclaimed land utilized an extensive system, which was deemed unsuitable given the land conditions and forage availability for livestock. Soil fertility status was classified as low, with forage production yields of 1,164.29 kg ha-1 in Pedok 3 and 984.04 kg ha-1 in Pedok 2. The land’s carrying capacity ranged from 23 to 27.02 AU year-1, based on an average livestock unit weight of 250 kg, equivalent to 23-27 adult Bali cattle